2022
DOI: 10.3390/ma15020407
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Plasma Sintering of NiAl-Al2O3 Composite Powder Produced by Mechanical Alloying with Contribution of Nanometric Al2O3 Powder

Abstract: NiAl-Al2O3 composites, fabricated from the prepared composite powders by mechanical alloying and then consolidated by pulse plasma sintering, were presented. The use of nanometric alumina powder for reinforcement of a synthetized intermetallic matrix was the innovative concept of this work. Moreover, this is the first reported attempt to use the Pulse Plasma Sintering (PPS) method to consolidate composite powder with the contribution of nanometric alumina powder. The composite powders consisting of the interme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 32 publications
(59 reference statements)
8
9
0
Order By: Relevance
“…Based on the histogram, it was found that the actual size of the powders was close to the manufacturer's stated size. Similar conclusions were obtained in previous work [17,28]. The SEM images of the metal powders are shown in Figure 4.…”
Section: Description Of the Raw Powderssupporting
confidence: 90%
See 2 more Smart Citations
“…Based on the histogram, it was found that the actual size of the powders was close to the manufacturer's stated size. Similar conclusions were obtained in previous work [17,28]. The SEM images of the metal powders are shown in Figure 4.…”
Section: Description Of the Raw Powderssupporting
confidence: 90%
“…The results of our own previously prepared works were concentrated on the preparation and characterization of NiAl-Al 2 O 3 composite powder. The composite powder was prepared by mechanical alloying from powder mixtures containing Ni-50 at.% and Al with a contribution of 10 wt.% or 20 wt.% of Al 2 O 3 [17]. However, positive attempts to use more than-30 wt.% Al 2 O 3 were also made.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 2 ] The composite design for cladding process focuses on low‐cost together with high‐performance material characteristics. The NiAl‐based material is prepared and investigated to develop various applications, including directed solidification, [ 3 ] casting, [ 4 ] mechanical alloying methods, [ 5 ] and additive manufacturing. [ 6 ]…”
Section: Introductionmentioning
confidence: 99%
“…[2] The composite design for cladding process focuses on low-cost together with highperformance material characteristics. The NiAl-based material is prepared and investigated to develop various applications, including directed solidification, [3] casting, [4] mechanical alloying methods, [5] and additive manufacturing. [6] The intermetallic compounds of NiAl are characterized by a B2 crystal structure and exhibit a combination of capabilities derived from both metallic and ceramic materials.…”
mentioning
confidence: 99%